THE MEDIATING ROLE OF TRUST: HOW CULTURAL FACTORS SHAPE CONSUMER ACCEPTANCE OF CHINESE ELECTRIC VEHICLES IN JAKARTA, INDONESIA - Kuswardani, Suci; Lawanda, Ike Iswary (UI Scholars Hub, 2026)
This study examines the mediating role of consumer trust in the relationship between cultural factors and the purchase intention of Chinese Electric Vehicles (EVs) in Jakarta, Indonesia. While global EV adoption is often analyzed through techno-economic lenses, this research addresses a critical gap by investigating the under-explored socio-cultural dimensions that shape consumer behavior in emerging markets. Framed by an integrated theoretical approach combining Hofstede’s Cultural Dimensions, the Technology Acceptance Model (TAM), and Reception Theory, the study explores how local cultural values such as collectivism, uncertainty avoidance, and social status filter the acceptance of Chinese EV technology. A qualitative case study methodology was employed, utilizing in-depth interviews and focus group discussions with nine key informants from multi-sector backgrounds (consumers, dealers, manufacturers, and government representatives). Thematic analysis was conducted to interpret the data. The findings reveal that while Jakarta consumers perceive Chinese EVs as useful due to economic and environmental benefits (perceived usefulness), adoption is significantly hindered by low perceived ease of use, primarily due to inadequate charging infrastructure and service networks. More importantly, cultural factors profoundly shape purchase intention: collectivist values emphasize social validation and peer influence, while high uncertainty avoidance fosters scepticism towards foreign product quality and safety. Consumer trust, built through social proof, hands-on experience, and reliable after-sales service, emerges as a critical mediating variable between these cultural perceptions and the final purchase decision. The study concludes that the acceptance of Chinese EVs in Jakarta is not merely a function of technological utility but a complex negotiation within the local cultural context. Effective market strategies must therefore adopt a multidimensional approach, integrating transparent quality assurances, culturally resonant communication, community-based marketing, and supportive government policies to build trust and align the product with local social values. This research contributes to cross-cultural marketing and technology acceptance literature by emphasizing the centrality of trust and cultural reception in the adoption of innovative foreign products in emerging markets.